1990
DOI: 10.1159/000186153
|View full text |Cite
|
Sign up to set email alerts
|

Protein C, Protein S, and Antithrombin III Levels in Patients on Continuous Ambulatory Peritoneal Dialysis and Hemodialysis

Abstract: Patients undergoing dialysis are subject to risk of thrombotic complications. We studied the plasma levels of natural coagulation inhibitors including protein C (PC), protein S (PS), and antithrombin III (AT III) in 20 patients on hemodialysis and 20 patients on continuous ambulatory peritoneal dialysis (CAPD). Total PS antigen, free PS antigen, immunological and functional activities of PC and AT III were measured. Hemodialysis patients had a higher total PS level but a lower free PS level compared with healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
2
9
1
Order By: Relevance
“…In our series of patients, factor VIII and fibrinogen levels were significantly higher in hemodialysis patients than in controls, whereas factor VII and factor IX levels were similar in patients and controls. In contrast to previous studies [7,33,34], we found no significant difference in the levels of natural coagulation inhibitors (AT, proteins C and S) between hemodialysis patients and controls. Decreases in the levels of natural coagulation inhibitors may result from hemodialysis itself or the type of underlying nephropathy, particularly for nephrotic syndrome [7,33,34].…”
Section: Discussioncontrasting
confidence: 99%
“…In our series of patients, factor VIII and fibrinogen levels were significantly higher in hemodialysis patients than in controls, whereas factor VII and factor IX levels were similar in patients and controls. In contrast to previous studies [7,33,34], we found no significant difference in the levels of natural coagulation inhibitors (AT, proteins C and S) between hemodialysis patients and controls. Decreases in the levels of natural coagulation inhibitors may result from hemodialysis itself or the type of underlying nephropathy, particularly for nephrotic syndrome [7,33,34].…”
Section: Discussioncontrasting
confidence: 99%
“…Continuous ambulatory peritoneal dialysis (CA PD ) does not routinely employ heparin. However, C A P D may result in the loss of natural anticoagulant factors and plasma coagulation fac tors [11,12] in the dialysate. Furthermore, platelet activation has been reported as a consequence o f hypo-albuminaemia and altered prostaglandin synthesis [13,14], Previously, the assessment of haemostasis and coagula tion in uraemia and the effect o f both haemodialysis and C A P D on these variables relied upon individual tests, such as the measurement of the plasma level of clotting factors, platelet adhesion to glass beads and platelet aggregation.…”
mentioning
confidence: 99%
“…3 Correlation between protein Z and fibrinogen levels (r=0.51; p<0.001) serum lipids, lipoprotein (a), and cytokines. On the contrary, Lai et al [26] reported that PD patients had higher plasma levels of PC, PS, and AT III than in HD patients despite greater daily losses through urinary and peritoneal routes. The authors suggested an effective turnover and production of these natural coagulation inhibitors in patients on PD therapy.…”
Section: Discussionmentioning
confidence: 94%
“…While some studies report a more hypercoagulable state in one dialysis modality some others suggest the opposite. Increased or normal levels of PS, PC and AT III have been reported in PD patients whereas PC and PS levels were found to be decreased in HD patients [5,7,[26][27][28]. Malyszko et al [29] reported a more hypercoagulable state in PD patients than in HD patients in their study investigating platelet aggregation, hemostatic parameters, Fig.…”
Section: Discussionmentioning
confidence: 99%